The Indonesia Triple Helix Digital Platform Model in Knowledge Sharing for Product Innovation Collaboration - Hakim, Shidiq Al; Sensuse, Dana Indra; Lestari, Puri Indah (DESIDOC Journal of Library & Information Technology, 2022)
The research gap between research institutions or universities and industry is still happening today. That arises because there has not been a maximum research collaboration between academic research and industry. This study aimed to develop a triple helix digital platform model in the product innovation ecosystem. Soft Systems Methodology (SSM) was chosen to conduct proposed scientific contributions in knowledge management in the triple helix digital platform model, especially knowledge sharing in product innovation. Data collected through the literature review and interview process with one researchers and two Small and Medium Enterprise (SME) owners, the seven stages of the SSM are used to analyse the results. This research resulted in a conceptual model and a prototype of a digital platform design with a strong foundation for knowledge sharing product innovation in the digital platform ecosystem. This prototype application will support collaboration between researchers and Small and Medium Industries to product innovation.